ANTIBACTERI ACTIVITY TEST OF ETANOL EXTRACT OF SEMBUNGLEAVES (Blumea balsamifera) ON THE GROWTH OF STAPHYLOCOCCUS AUREUS BACTERIES BY USING THE CAKRAM METHODS - Dona Muin; Supriadi; Isma Ayu Natasa (Poltekkes Kemenkes Banten, 2026)
Staphylococcus aureus is a harmful type of bacteria. Infectious diseases caused by these bacteria are boils, acne, and skin infection. Sembung leaves (Blumea balsamifera) have secondary metabolite compounds such as flavonoids, alkaloids, tannins and steroids that have potential as antibacterials. The purpose of this study was to determine the antibacterial activity of ethanol extract of Sembung leaves (Blumea balsamifera) with concentrations of 10%, 25%, and 50% against the growth of Staphylococcus aureus bacteria with the disc method. This type of research is Quasy experimental antibacterial tests carried out by making paper disks that are dripped with extracts with concentrations of 10%, 25%, 50% and to determine the concentration with the greatest inhibitory effect. Extraction was carried out by maceration method using 96% ethanol solvent. Inhibition testing of ethanol extract of Sembung leaf (Blumea balsamifera) was done by disc method. Positive control used chloramphenicol. The results showed the average number of inhibition zones of 10% concentration (11.6) mm, 25% concentration (13.3) mm, 50% concentration (14.6) mm, the positive control produced an inhibition zone of 20 mm categorized as very strong, while the negative control did not form an inhibition zone. Based on the research that has been done, it can be concluded that the inhibition at a concentration of 50% gives the greatest inhibitory effect.